WEE1 kinase inhibition reverses G2/M cell cycle checkpoint activation to sensitize cancer cells to immunotherapy. (3rd October 2018) - Sun, Lillian; Moore, Ellen; Berman, Rose; Clavijo, Paul E.; Saleh, Anthony; Chen, Zhong; Van Waes, Carter; Davies, John; Friedman, Jay; Allen, Clint T.
ABSTRACT: Intrinsic resistance to cytotoxic T-lymphocyte (CTL) killing limits responses to immune activating anti-cancer therapies. Here, we established that activation of the G2/M cell cycle checkpoint results in tumor cell cycle pause and protection from granzyme B-induced cell death. This was reversed with WEE1 kinase inhibition, leading to enhanced CTL killing of antigen-positive tumor cells. Similarly, but at a later time point, cell cycle pause following TNFα exposure was reversed with WEE1 kinase inhibition, leading to CTL transmembrane TNFα-dependent induction of apoptosis and necroptosis in bystander antigen-negative tumor cells. Results were reproducible in models of oral cavity carcinoma, melanoma and colon adenocarcinoma harboring variable Tp53 genomic alterations. WEE1 kinase inhibition sensitized tumors to PD-1 mAb immune checkpoint blockade in vivo, resulting in CD8 + -dependent rejection of established tumors harboring antigen-positive or mixed antigen-positive and negative tumor cells. Together, these data describe activation of the G2/M cell cycle checkpoint in response to early and late CTL products as a mechanism of resistance to CTL killing, and provide pre-clinical rationale for the clinical combination of agents that inhibit cell cycle checkpoints and activate anti-tumor immunity.